ANALISIS NILAI KARAKTER TEKS DESKRIPSI DALAM BUKU BAHASA INDONESIA PADA SISWA MTS - Rani Nurmalasari; Wike Anggraeni; Rochmat Tri Sudrajat (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research aims to 1) to analyze the values contained in the text of the descriptions in the indonesian textbook revision of 2017 high school students/ MTs. 2) the implication of the character  value in the description text for the learner. This type of reseacrh a qualitative description. Population text analysis of this description are  examples of  descriptive text contained in the book “bahasa indonesia SMP/MTs”. Text contained in the book of 6 texts. Among others “beautiful parangkritis, my father, my inspiration mother, my rabbit bagel, the fascinating beach charm and the gigantion of colossal dance performances”. Data collections technique is done by reading technique. Are done by identifying data, classifiying data, and describing data. The results of the reseach note that the text of the descriptions contained in the book bahasa indonesia SMP/MTs three are 6 descriptions text containing 12 values of characters such as religious, pround, patient, quiet, exemplary, friendly,soft, persistent, good, spoiled, interesting, preservation and emotional. The   value of the character impacts (1) fosters the positive character that is embedded in them, (2) cultivate a sense of pride in the country, (3) cultivate a sense of empathy, (4) enhance hisreligious nature the creator, (5)  active in studying.  Keywords: description text, Character Value